Climate Change: A Pre-Service Teachers’ Intervention Program - Anat Abramovich; Sophie Shauli (Australian Journal of Environmental Education)
This study examined the impact of a short-term climate literacy (CL) course on pre-service teachers (PSTs) at a local college in Israel. Thirty-six science and communication PSTs participated. Using a mixed methods approach, pre and post-course questionnaires and assignment responses showed significant improvements in climate change knowledge and environmentally responsible behaviour (ERB) after the course. PSTs’ attitudes were key predictors of their ERB. The qualitative analysis supported these findings, revealing that the participants who were able to express complex climate knowledge also intended to reflect more environmentally responsible behaviour. 52.2% of participants with complex climate knowledge used diverse knowledge types to express ideas, reflecting a real commitment to environmental attitudes and personal behaviour. While 65% raised climate awareness within their families, only 33% discussed it, during their practicum, with students. Overall, the course significantly enhanced PSTs’ climate literacy in knowledge, attitudes and behaviour, even as a limited workshop. According to the findings, courses that promote climate literacy are necessary. The findings of this study indicate that a well-established short-term intervention may affect participants regarding a significant issue like climate change.